1934 N.J. Laws 394-95, ch. 155, §§ 1-5 - (:unkn) unknown (General Publisher, 1934)
Declares a person who possesses a machine gun or submachine gun a “gangster” and therefore, enemy of the state. Also declares a person who carries a deadly weapon without a permit a “gangster.” If convicted a “gangster,” punishable by fine up to $10,000 and/or imprisonment up to 20 years.
--
Keywords: MACHINE GUN RESTRICTION